The ellagitannin trimer rugosin G inhibits recombinant human histidine decarboxylase. Issue 7 (3rd July 2019) - Nitta, Yoko; Ito, Hideyuki; Komori, Hirohumi; Ueno, Hiroshi; Takeshima, Daiki; Ito, Mikiko; Sakaue, Motoyoshi; Kikuzaki, Hiroe
ABSTRACT: Rugosin G, an ellagitannin trimer, was isolated from the water-soluble fraction of red rose petals, and its inhibitory activity against recombinant human histidine decarboxylase was investigated. Rugosin G showed potent inhibition compared to ellagitannin monomers and a dimer with macrocyclic structure (oenothein B), suggesting the potent inhibition of rugosin G was attributed to its linear oligomeric conformation. Abbreviations: HDC, histidine decarboxylase; Me2 CO, acetone; EtOAc, ethyl acetate